Penerjemahan Kalimat Kondisional Bahasa Indonesia ke dalam Bahasa Inggris: Kajian Sintaksis dan Semantik - Nurhayati, Iis Kurnia (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
Unlike English that divides its conditional sentences into open and hypothetical types, there is no division of conditional sentence types in Indonesian. Hence, translating conditional sentences from Indonesian to English is challenging. The purpose of this study was to determine the equivalence of meaning and structure of the conditional sentences in the source language (Indonesian) and the target language (English) in Pramoedya Ananta Toer’s novel, *Gadis Pantai*, and its English translation. As this novel is a literary work, the complexity of the structure of the conditional sentence in this novel is very interesting to study. The method used in this study is comparative descriptive, which was employed to provide clear pictures of the discussed issues. The findings of the study show that in translating the conditional sentence from Bahasa Indonesia into English in the novels, the translator has made some adjustments both in the sentence structure and meaning due to the significant differences of the social-cultural aspect between the source and the target language.